Presence of a soluble form of acetylcholinesterase in human ocular fluids. Issue 5 (May 1991) - Appleyard, M. E.; McDonald, B.; Benjamin, L.
Abstract : Samples of ocular fluid obtained from normal persons at necropsy and during eye surgery have been assayed for the presence of acetylcholinesterase. Measurable levels could be detected in all samples examined, but levels of acetylcholinesterase in vitreous humour were consistently higher than those in aqueous humour, indicating a possible retinal origin. Polyacrylamide gel electrophoresis revealed that the enzyme of ocular fluid had the same mobility as that of acetylcholinesterase from cerebrospinal fluid. It is probable that acetylcholinesterase is secreted from neuronal structures in the retina into the ocular fluid in an analogous manner to the secretion of acetylcholinesterase from brain neurones into cerebrospinal fluid.